A canonical model for interactive unawareness - Aviad Heifetz; Martin Meier; Burkhard C. Schipper (University of California, Department of Economics, 2005)
Heifetz, Meier and Schipper (2005) introduced a generalized state-space model that allows for non-trivial unawareness among several individuals and strong properties of knowledge. We show that this generalized state-space model arises naturally if states consist of maximally consistent sets of formulas in an appropriate logical formulation.
Keywords: C70; C72; D80; D82; 330